Safe Tractor Operations: Loading and Towing - Serap Gorucu; Carol J. Lehtola; Charles M. Brown (EDIS, 2024)
The Safe Tractor Operations series contains six articles devoted to tractor safety. This publication lists safety recommendations for towing equipment and loading a tractor onto a trailer or truck. Written by Serap Gorucu, Carol J. Lehtola, and Charles M. Brown and published by the UF/IFAS Department of Agricultural and Biological Engineering, June 2024.